2010
DOI: 10.2486/indhealth.48.296
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Mechanical Filters and Respirators for Capturing Nanoparticles ―Limitations and Future Direction

Abstract: There is an increasing concern about the health hazard posed to workers exposed to inhalation of nanoparticles. Inhaling nanoparticles posses an occupational hazard due to elevated amount emitted to the atmosphere and working environment. Nanoparticles have potential toxic properties: the high particle surface area, number concentration, and surface reactivity. Inhalation, the most common route of nanoparticle exposure, has been shown to cause adverse effects on pulmonary functions and the deposited particles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 48 publications
0
41
0
Order By: Relevance
“…This result is as expected considering the established filtration theory: Hinds (1999) and Lee and Liu (1980) determined that the effects of interception and inertial impaction increase with particles size, while the effect of Brownian diffusion decreases with particle size. Moreover, Mostofi et al (2010) and Kousaka et al (1989) noted that increasing air velocity substantially decreases the effect of diffusion, while it does not influence the effect of interception. The effect of impaction increases with air velocity, but this mechanism mainly influences particles larger than the upper particle size measured in the present experiments.…”
Section: Influence Of the Air Velocitymentioning
confidence: 99%
See 2 more Smart Citations
“…This result is as expected considering the established filtration theory: Hinds (1999) and Lee and Liu (1980) determined that the effects of interception and inertial impaction increase with particles size, while the effect of Brownian diffusion decreases with particle size. Moreover, Mostofi et al (2010) and Kousaka et al (1989) noted that increasing air velocity substantially decreases the effect of diffusion, while it does not influence the effect of interception. The effect of impaction increases with air velocity, but this mechanism mainly influences particles larger than the upper particle size measured in the present experiments.…”
Section: Influence Of the Air Velocitymentioning
confidence: 99%
“…Published results are diverging, but it is indicated that the thermal rebound effect mainly affects particles of a few nanometers in size. A review of papers dedicated to the study of thermal rebound can be found in Mostofi et al (2010). However, this issue is out of the scope of the present investigation, which comprises measurement of particles sized above 14 nm.…”
Section: Filtration Efficiency Of Intermediate Class Filters 489mentioning
confidence: 99%
See 1 more Smart Citation
“…The media #A, #C and #E show a minimum number efficiency with higher than 95%, therefore, they could be regarded as N-95 respirator media (Mostofi et al, 2010). The curves presented in Fig.…”
Section: Bimodal Pm Size Distributionmentioning
confidence: 99%
“…However, electret media are commonly applied in the respirators to reduce the flow resistance to achieve a better comfort of wear. But it has been found there is high penetration occurring in both nano-sized (20-50 nm) and submicron-meter or micro-meter size range in electret filter media (Lathrache et al, 1986;Lathrache and Fissan, 1987;Mostofi et al, 2010;Rengasamy et al, 2010;Chen et al, 2014). Therefore, to evaluate respirators filters with more realistic bimodal PMs is essential.…”
Section: Introductionmentioning
confidence: 99%